A serial mediation model of negative life events on school adjustment of left-behind adolescents in rural China: the central role of hope and gratitude - Zhang, Lyuci; Roslan, Samsilah; Zaremohzzabieh, Zeinab; Liu, Kexin; Tang, Xing; Jiang, Yuqin; Mohamad, Zulkifli (BioMed Central, 2023)
Adjustment difculties of school students are common and their school adjustment has gained wide concern in recent years. Negative life events (NLEs) hope, and gratitude have been associated with school adjustment. However, the potential efect of NLEs on hope and gratitude and whether hope and gratitude mediate the association between NLEs and school adjustment among high students have not been studied. Thus, this study aims to investigate the association between NLEs, hope and gratitude, and school adjustment in high school students in China. Additionally, the study aims to examine the mediating role of hope and gratitude in the association between NLEs and school adjustment. A total of 700 junior high school students in Guangxi Province (336 boys, 364 girls, M age=15 years) completed the questionnaire. The results indicated signifcant mediating efects of hope and gratitude in the sequential positive association between NLEs and school adjustment. Furthermore, this study unraveled the complexity of the link between NLEs and school adjustment with the combination of hope and gratitude. The fndings emphasized the importance of fostering hope and gratitude in left-behind adolescents to combat the negative consequences of NLEs. The study is also one of the frst to investigate a serial mediation model to determine which NLEs infuence Chinese left-behind adolescents school adjustment.